Pengembangan dan Validasi Andana Responding Activity in Learning Scale (ARALS) - Rizky Andana Pohan (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2021)
This study aims to develop and validate the Andana Responding Activity in Learning Scale (ARALS). This inventory will measure student response activities in learning. The response aspects that will be measured by this inventory are the activities of asking, answering and expressing opinions on the learning process that takes place based on the response theory put forward by Elliot et al. (1996) and Prayitno (2002). This research was conducted on 50 high school students using simple random sampling technique. Validity test using product moment correlation obtained 16 valid items with an overall validity value of 0.672. Furthermore, the instrument reliability test was carried out using the Croncbach Alpha formula, the coefficient value obtained was 0.921. The results of this study indicate that ARALS can be used by teachers/ school counselors to measure and understand students' conditions in responding to learning activities and are ready to be used for further research.